The Effect of Nature-Based Creative Dance on Gross Motor Development in Early Childhood - Ahda Nazib; Nur Hazizah (Darul Yasin Al Sys, 2026)
Although early childhood gross motor development has received considerable attention in previous studies, research specifically examining natural movement-based creative dance as a contextual learning approach remains limited. This study aims to analyze the effect of natural movement-based creative dance on the gross motor development of children aged 5–6 years. A quantitative approach with a quasi-experimental non-equivalent control group design was employed, involving 30 children selected through purposive sampling. Data were collected using gross motor development observation sheets that had been tested for validity and reliability and were analyzed using an independent samples t-test. The results showed a significant difference between the experimental and control groups (p < 0.05), with a greater increase in gross motor scores among children who received the natural movement-based creative dance treatment. These findings indicate that dance activities grounded in natural movements are effective in improving children’s balance, coordination, and agility. The study contributes to the strengthening of motor development theory by emphasizing the importance of contextual and meaningful physical activity-based stimulation. It concludes that natural movement-based creative dance is an effective and innovative learning strategy for optimizing early childhood gross motor development. Therefore, early childhood educators are encouraged to integrate this approach into learning activities. The implications of this research include theoretical contributions to the development of movement-based learning and practical recommendations for teachers in designing more creative and contextual activities. Further research is recommended to explore the long-term effects of this approach and its integration with other aspects of child development.